Pengaruh Servant Leadership Terhadap Organizational Citizenship Behavior (OCB) dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Pada Pegawai BKPSDM Kabupaten Klaten) - Monica, Rosa Lingga; Partina, Anna (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This study aims to analyze the effect of servant leadership on organizational citizenship behavior with job satisfaction as a mediating variable. The sample in this study were all employees of BKPSDM Klaten Regency totaling 39 employees. The sampling technique used non probability sampling technique with saturated sample method. Data collection was carried out by distributing questionnaires directly to respondents. Hypothesis testing using path analysis with IBM SPSS Statistics 26 analysis tools. The results showed that servant leadership has a positive effect on organizational citizenship behavior, servant leadership has a positive effect on job satisfaction, job satisfaction has no effect on organizational citizenship behavior, job satisfaction does not mediate the effect of servant leadership on organizational citizenship behavior.